Some stationary properties of a Q-ball in arbitrary space dimensions - Tsumagari, Mitsuo I.; Copeland, Edmund J.; Saffin, Paul M. (American Physical Society, 2008)
Introducing new physically motivated ansaetze, we explore both analytically and numerically the classical and absolute stabilities of a single Q-ball in an arbitrary number of spatial dimensions D, working in both the thin and thick wall limits.